Digital Protection Of Power Transformer Using Microcontroller-Based Relay - Rafa, Adel Hamad (2002)
In this thesis the fault types m the power transformer as well as their protection scheme have been studied, and the factors which lead to mal operation of differential protection such as : magnetizing inrush, over excitation, ratio mismatch and current transformer saturation have been investigated. The existing methods of discriminating internal faults from inrush magnetizing condition have been reviewed. A method to discriminate internal fault from inrush current depended on the rate of change of primary current with respect to time at the first quarter cycle has been used in this work. The percentage differential protection, over current protection, over voltage protection and under voltage protection are implemented m a microcontroller-based system. The design implementation and testing of the system are also presented. The performance of the system was checked in the laboratory. The experimental results gave a good agreement with the theoretical ones.